A Review of Oxytocin and Arginine-Vasopressin Receptors and Their Modulation of Autism Spectrum Disorder - Cataldo, Ilaria; Azhari, Atiqah; Esposito, Gianluca (Frontiers in Molecular Neuroscience, 2018)
Oxytocin (OXT) and arginine-vasopressin (AVP) play a key regulatory part in social and affiliative behaviors; two aspects highly compromised in Autism Spectrum Disorder (ASD). Furthermore, variants in the adjacent oxytocin-vasopressin gene regions have been found to be associated with ASD diagnosis and endophenotypes. This review focuses mainly on common OXTr single nucleotide polymorphisms, AVPR1a microsatellites and AVPR1b polymorphisms in relation to the development of autism. Although these genes did not surface in genome-wide association studies, evidence supports the hypothesis that these receptors and their polymorphisms are widely involved in the regulation of social behavior, and in modulating neural and physiological pathways contributing to the etiology of autism spectrum disorder (ASD). With a specific focus on variants considered to be among the most prevalent in the development of ASD, these issues will be discussed in-depth and suggestions to approach inconsistencies in the present literature will be provided. Translational implications and future directions are deliberated from a short-term and a forward-looking perspective. While the scientific community has made significant progress in enhancing our understanding of ASD, more research is required for the ontology of this disorder to be fully elucidated. By supplementing information related to genetics, highlighting the differences across male and female sexes, this review provides a wider view of the current state of knowledge of OXTr and AVPr mechanisms of functioning, eventually addressing future research in the identification of further risk factors, to build new strategies for early interventions.